Nursing assistance during childcare in light of the theory of comfort (Research, Society and Development, 2022)
Objective: To reflect on the applicability of the Kolcaba Comfort theory for Nursing care to children during childcare. Method: Theoretical-reflective study, based on a critical reading of nursing theories, nursing care in childcare and the need to discuss the training of nurses in this perspective. Results: Kolcaba's theory of comfort is a medium-range theory that can be applied to the practice of nursing professionals in pediatrics, since it has a theoretical framework that invigorates nursing as a science, in addition to being associated and grounded in the process of nursing. The theory establishes two dimensions for comfort: the first referring to states of comfort, which include relief, tranquility and transcendence; and the second dimension referring to the physical, psycho-spiritual, sociocultural and environmental contexts in which comfort is inserted. Conclusion: The comfort theory presents itself as a theoretical framework of easy application for child health. From the use of this theory, nursing recognizes the child's needs, promoting comfort and, consequently, health care.